Job seekers with musculoskeletal or sensory disabilities: Barriers and facilitators of job search - Fujimoto, Yuka * (2018)
Drawing on interviews with job seekers and expert informants, we outline a model of the job search experience of people with disabilities. This model outlines the sequence of events involved in the pursuit of paid work and the contextual features that inhibit or facilitate job search attitudes, behaviours, intermediate search outcomes, and employment outcomes. By contrasting the experiences of job seekers with musculoskeletal and sensory disabilities, and outlining the influence of major stakeholders in the form of employment agencies and family members, our model provides the basis for a more nuanced understanding of the job search process. Finally, we recommend points of intervention that are grounded in data for improving job search outcomes for people with disabilities in general, and for job seekers with musculoskeletal or sensory disabilities specifically.